Research on Knowledge Navigation Model Based on Users’ Tolerance Zone During the Process of R&D Achievements Delivery - Tao, Na (International journal of innovation and technology management, 2022)
How to promote deep knowledge transfer and knowledge application during the process of R&D achievements delivery? This paper takes knowledge transfer as the research object. First of all, the path of knowledge transfer during the process of R&D achievements delivery is drawn. Next, the status of knowledge transfer is assessed by constructing users’ tolerance zone model by selecting key factors in the path of knowledge transfer. Empirical research finds the following conclusions: knowledge transfer experience − actual , knowledge transfer distance and knowledge transfer carrier have a positive influence on the actual service level of knowledge transfer. Knowledge transfer experience − ideal , continuous strengthening behavior and knowledge service commitment have a positive impact on the ideal service level of knowledge transfer. Then, based on knowledge transfer path and users’ tolerance zone model, this paper explores the knowledge navigation model from the environment, main structure and transmission mode. Finally, from the perspective of knowledge transfer environment, knowledge transfer subject, knowledge transfer object and knowledge transfer mode, the relevant strategies were put forward to reduce knowledge retention, and promote the deep knowledge absorption and transformation during the process of R&D achievements delivery.